Water next Tuesday: eLEAF's irrigation-advice service in the Gezira Scheme in Sudan - Dost, Remco; Khalifa, Amgad (Technical Centre for Agricultural and Rural Cooperation, 2017)
Many people in Sudan communicate with text messages on their mobile phones – mostly with friends and family. But a small number of farmers in the Gezira irrigation scheme, near Khartoum, are testing a new service: a weekly SMS that tells them when to irrigate their crops. The 44 farmers have taken part in a pilot project with support from CTA. The project tested an ingenious idea: it monitored the water needs of the farmers’ crops by satellite and sent them a message telling them when to irrigate. The advice came as a clear instruction such as “you need to irrigate 5 days from now.” Such instructions are especially useful for the many farmers in the area who hold other jobs and cultivate their land part-time.